2007
DOI: 10.1007/bf03022769
|View full text |Cite
|
Sign up to set email alerts
|

Early oral analgesia after fast-track cardiac anesthesia

Abstract: Purpose: Oral analgesia after "fast-track" cardiac anesthesia has not been explored. The aim of this study was to compare two oral oxycodone analgesic regimens. Methods:One hundred-twenty patients scheduled for coronary artery bypass grafting were randomly assigned postoperatively to receive immediate-release oxycodone 5 mg and acetaminophen 325 mg (Percocet-5) (group I) per os four times daily, or controlled-release oxycodone 10 mg (OxyContin) (group II) per os every 12 hr and placebo twice daily. Acetaminoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 35 publications
(30 reference statements)
0
36
0
1
Order By: Relevance
“…http://onlinelibrary.wiley.com/doi/10.1111/pme.12233/suppinfo illustrates the study designs and patient characteristics of the component studies of this literature review. Of the 68 studies included in the literature review, the majority (k = 65) were clinical trials (i.e., randomized or open‐label) [12,15–73]. The remaining three studies were observational [74–76].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…http://onlinelibrary.wiley.com/doi/10.1111/pme.12233/suppinfo illustrates the study designs and patient characteristics of the component studies of this literature review. Of the 68 studies included in the literature review, the majority (k = 65) were clinical trials (i.e., randomized or open‐label) [12,15–73]. The remaining three studies were observational [74–76].…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐four studies assessed the effects of LAOs (oxycodone [N = 13], fentanyl [N = 2], morphine [N = 19], tramadol [N = 8], methadone [N = 0], oxymorphone [N = 8]) [12,15–23,27,29,30,35,36,48–66,68–79], among which were six studies were with ADFs (morphine sulfate and naltrexone hydrochloride ER [N = 6]; oxycodone hydrochloride ER [N = 2]) [29,30,52,53,61,63,64,73]. Twenty‐two studies assessed the effects of SAOs (hydrocodone [N = 1], oxycodone [N = 13], tramadol [N = 7], codeine [N = 0]) [24–26,28,31–34,37–47,67,80,81], of which one study had an ADF as an active treatment (oxycodone hydrochloride controlled‐release [N = 1]) [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the bioavailability of gabapentin decreases with increasing dose; therefore, we chose gabapentin(300mg) as the experimental dose. Kogan A1 et al [21] found that oxycodone-acetaminophen (5mg / 325mg) has better analgesic effect and less side effects than sustained-release oxycodone (10mg) in oral surgery EARS anesthesia.Davis KM et al [22] found that oral analgesia with oxycodone-acetaminophen may offer superior pain after cesarean delivery with fewer side-effects as compared with morphine patientcontrolled analgesia.A meta-analysis [23] showed that high doses of oxycodone-acetaminophen were associated with an increase in analgesic-related adverse events, but these adverse events were often described as mild or moderate and were not associated with withdrawal. Therefore, we chose oxycodone-acetaminophen(330 mg) containing oxycodone(5mg) and acetaminophen(325mg).…”
Section: Discussionmentioning
confidence: 99%
“…Eine Vielzahl von Untersuchungen konnte in den letzten Jahren zeigen, dass die planmäßige und zeitlich begrenz te orale Gabe retardierter, starker Opi oide eine wirksame Therapiemöglich keit postoperativer Schmerzen darstellen kann [2,3,5,6,12]. Insbesondere der Ein satz von retardiertem Oxycodon (z.…”
unclassified